Denialism and the Death Penalty - Condon, Jenny-Brooke (2020)
The persistence of capital punishment as a constitutional form of punishment in the United States reflects deep denialism about the practice and the role of the courts in regulating it. Denialism allows judges to embrace empirically contested narratives about the death penalty within judicial decisions, to sanction execution methods that shield and distort the pain associated with state killing, and to ignore the documented influence of race on the death penalty’s administration. This Article draws upon the concept of denialism from the transitional justice context, a theory that explicates denial in responses to mass human rights violations and collective violence. It describes mechanisms of denial in judicial regulation of capital punishment and argues that conditions will not be ripe for judicial abolition of the death penalty until this denialism is better understood and confronted. I identify potential entry points for exposing and overcoming denialism in Eighth Amendment analysis